Predation on lesser bulldog bat (Noctilio albiventris Noctilionidae) by great Rufous Woodcreeper (Xiphocolaptes major Dendrocolaptidae) - Camargo, Paulo H.S.A. [UNESP]; Laps, Rudi R. (Taylor & Francis, 2016)
The Great Rufous Woodcreeper (Xiphocolaptes major) feeds mostly on arthropods, but includes small vertebrates such as amphibians and reptiles in its diet, as well as eggs and nestlings of other songbirds. There are a few records of bats in the diet of the Great Rufous Woodcreeper, but it is not known how commonly they consume bats. During fieldwork in the Brazilian Pantanal, we recorded a Great Rufous Woodcreeper preying on a lesser bulldog bat (Noctilio albiventris). After striking the bat, the woodcreeper ingested thin strips of the prey's flesh. The use of tree cavities by the bats and Great Rufous Woodcreeper in the Pantanal may increase the chance of encounters between woodcreepers and bats, and suggests that this kind of predation event involving these two groups may be more common than reported.
Keywords: Brazilian Pantanal; cavities; diet; feeding behavior; Noctilio; opportunistic predation; vertebrate predation